Contextualization of Islamic Education Curriculum in Junior High Schools - Abitolkha, Amir Maliki; Ismail, Ahmad Nur; hady, Yazid (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
AbstractSeveral years of experience teaching PLPG training for teachers in the Ministry of Religion, especially Islamic Religious Education (PAI) teachers, found the fact that